Saving private Ryan. - Spielberg, Steven (Quezon City : Magnavision.)
Internationally acclaimed by critics and audiences alike, Steven Spielberg's Saving Private Ryan is an unforgettable film achievement that has had profound and lasting impact throughout the world. Winner of five Academy Awards including Best Director, the film also captured Oscars for Cinematography, Film Editing Sound and Sound Effects Editing. More than 70 critics (including those at time magazine, USA Today, The New York Times and Entertainment Weekly) and critics' groups in New York, Chicago, Dallas-Ft. Worth and Great Britain named the film Best Picture of the year, while the Los Angeles, Toronto and Broadcast Film Critics honored it with both Best Picture and Best Director awards. In addition, Spielberg received his third Directors Guild of American Award, the American Legion "The Spirit of Normandy" Award, a USO Merit Award from the USO of Metropolitan Washington, as well as the highest civilian public service award from the Depertment of the Army. Selected for men than 160 top Ten lists. Saving Private Ryan's other honor include Golden Globe for Best Picture (Drama) and Best Director, the Producers Guild of America Award and ten nominations from the British Academy Film Awards. Saving Private Ryan was the top-grossing motion picture of 1998. Seen through the eyes of a squad American soldiers, the story with World War II's historic D-Day invasion, then moves beyond the beach as the men embark on a dangerous special mission. Captain John Miller (Tom Hanks) must take his men behind enemy lines to find Private James Ryan, whose three brothers have been killed in combat. Faced with impossible odds, the men questions their orders. Why are eight men risking their lives to save just one? Surrounded by the brutal realities of war, each man searches for his own answer - and the strength triumph over an uncertain future with honor democracy and courage.